Respuesta :
The pattern that matches your examples is ...
... a + (b + c) = (a + b) + c
Answer:
a + (b + c) = (a + b) + c
Step-by-step explanation:
Given :
1. (5 + 2) + 3 = 5 + (2 + 3)
2. 3.5 + (1.2 + 9.6) = (3.5 + 1.2) + 9.6
To Find :choose the statement that best describes the property.
Solution :
Option b best describes the property
in 1. if take 5 as a 2 as b and 3 as c
Now put these values in option b
a + (b + c) = (a + b) + c
= 5 + (2 + 3) = (5 + 2) + 3
Thus option b satisfies
in 2. if take 3.5 as a 1.2 as b and 9.6 as c
Now put these values in option b
a + (b + c) = (a + b) + c
3.5 + (1.2 + 9.6) = (3.5 + 1.2) + 9.6
Thus option b satisfies
Hence Option b is correct